Free subsemigroups in automorphism group of a polynomial ring of two variables over number fields - Dovghey, Zh.; Sumaryuk, M. (Carpathian Mathematical Publications, 2011)
Sufficient conditions under which the semigroup generated by two automorphism of the polynomial ring in two variables over a number field P will be free are given. The set of free finitely generated subsemigroups of the triangle automorphism subgroup in AutP[x,y] and the set of non-free finitely generated of semigroups of this groups are compared in categorial sense of Baire.